146k views
0 votes
3(a− 6) = −5a− (7 + 3a)

User Valdrinium
by
5.4k points

1 Answer

4 votes

Answer:

A= 1

Explanation:

Distribute

3 ( − 6 ) = − 5 − 1 ( 7 + 3 )

3a - 18 = -5a - 1 ( 7 + 3a )

Rearrange terms

3 − 1 8 = − 5 − 1 ( 3 + 7 )

3a - 18 = -5a - 3a - 7

Combine like terms

3 − 1 8 = −5 − 3 − 7

3a - 18 = -8a - 7

Add 1 8 to both sides of the equation

3a - 18 = -8a - 7

3 − 1 8 + 1 8 = − 8 − 7 + 1 8

Simplify

Add the numbers

3 − 1 8 + 1 8 = − 8 − 7 + 1 8

3a = -8a - 7 + 18

Add the numbers again

3 = − 8 − 7 + 1 8

3a = -8a + 11

Add 8 to both sides of the equation

3a = -8a + 11

3 + 8 = − 8 + 1 1 + 8

Simplify

Combine like terms

3 + 8 = − 8 + 1 1 + 8

1 1 = − 8 + 1 1 + 8

Combine like terms again

1 1 = − 8 + 1 1 + 8

11a = 11

Divide both sides of the equation by the same term

11a = 11

1 1 / 1 1 = 1 1 / 1 1

Simplify

Cancel terms that are in both the numerator and denominator

1 1 / 1 1 = 1 1 / 1 1

a = 11/11

Divide the numbers

a = 11/11

a = 1

User Sophie Gage
by
5.2k points